Complexities in the Development of Maritime Transport Through Special Autonomy Funds - Viktor Fransiskus Salossa; Muh. Akmal Ibrahim; Muh. Thahir Haning (Journal La Sociale, 2025)
The development of maritime transport is influenced not only by governance structures, but also by the complexity of policies arising from the interaction of various interrelated factors. In practice, policies often have cross-regional impacts, face funding constraints, and are supported by data systems that are not yet integrated. This study aims to analyse the complexity in the development of maritime transport through the Special Autonomy Fund in South Sorong Regency. The research employs a qualitative approach using a case study strategy. Data were collected through interviews, observations, and documentation, and subsequently analysed using an interactive model. The findings reveal that policy complexity is reflected in three key aspects. Firstly, externalities and spillover effects that result in uneven policy impacts across regions. Secondly, limited funding mechanisms that rely on higher levels of government. Third, data fragmentation hinders evidence-based decision-making processes. These three aspects interact with one another and form systemic complexity in policy governance. Policy complexity requires a more integrative and adaptive approach. Policy management cannot be carried out in a linear manner, but must be able to accommodate interactions between factors within a dynamic system.